2005
DOI: 10.1007/s11178-005-0282-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Temperature Effects on the Reaction Rate of Aryloxiranes with 3,5-Dinitrobenzoic Acid in Acetonitrile

Abstract: The effects of temperature and structure of aryloxiranes on the rate of their reaction with 3,5-dinitrobenzoic acid in acetonitrile are additive, and the process is entropy-controlled.Reactions accompanied by opening of oxirane ring have long attracted researchers' attention due to their diversity, specificity of their mechanisms under catalytic and noncatalytic conditions, and wide application in organic synthesis (in particular, in the preparation of polymeric epoxy compounds [1][2][3][4][5][6]. An important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…26 Since the reaction is first order in the oxirane and second order in the acid, it has been suggested that pre-equilibrium association with HA is followed by attack of a second HA at the benzyl carbon. The much slower rate found when a more electron-withdrawing substituent is on the aryl ring was due to a large decrease in S = (i.e.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%
“…26 Since the reaction is first order in the oxirane and second order in the acid, it has been suggested that pre-equilibrium association with HA is followed by attack of a second HA at the benzyl carbon. The much slower rate found when a more electron-withdrawing substituent is on the aryl ring was due to a large decrease in S = (i.e.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%